Physical and chemical characteristics of limestone for use in layer feeds in Kenya - Inoti, D K; Mbugua, P N; Gachuiri, C K; Maina, J G (Indian Journal of Animal Nutrition, 2020)
An adequate amount of calcium (Ca)  is required by laying hens for eggshell formation and other physiological functions. There are many common sources of Ca. The  choice and use of each source depends on availability, cost and risk factors present. In Kenya, limestone is the main Ca source used in  layers’ feeds and is obtained from two main areas, Ukunda in the Kenya South coast (UKC) and Athi River (AR) near Nairobi. There is inadequate information on the physical, chemical and nutritional attributes of these limestone sources. The objective of this study was to determine the physical and chemical attributes of limestone from the two sources. Limestone from  two sources was purchased from a raw material vendor in Nairobi and in vitro solubility, acid insoluble ash (AIA) and mineral content were determined.  In vitro solubility of UKC and AR limestone was 63.4 and 39.43%, respectively. AR limestone had a high content of AIA at 23.17% as compared to 3.39% for UKC limestone explaining the difference in solubility. The particle size in limestone was classified into coarse (1-2mm), medium (0.5mm) and fine (0.125-0.5 mm). The proportion of particles in UKC and AR in that order was: coarse 22.6% and 9.9%, medium 17.4, and 28.6% and fine 29.2% and 41.9%. Silt (< 0.063mm) formed 17.8 and 10.0% of   UKC and AR limestone, respectively. Ca content in UKC limestone was 420 g/kg while in AR it was 340 g/kg. Cr, CU and Zn were found in small concentrations ranging from 0.3 to 8.6 μ/kg in UKC and AR limestone. Fe concentration was 42.6 and 53.6 μg/kg in UKC and AR respectively.  Aluminium was relatively high at 1073 and 302 μg/kg for UKC and AR, respectively.  Based on Ca and AIA content, solubility, and particle size UKC limestone is a superior Ca source than AR.